(untitled) (International Journal of Engineering and Computer Science, 2018)
Information security is an important issue in network communication. Because of the significance, accuracy and sensitivity of the information it is a big security and privacy issue, making it necessary to find appropriate solution, security and privacy has become as important concern. Cryptography is making sure to secured data protection. Cryptography concept is used facilitate for secret communication among the military communications. The present days different types of cryptography algorithm are used to secure data such AES, DES and blowfish. The traditional algorithms have some of the drawbacks like speed, key size and performance. The proposed a new cryptographic algorithm named as KDDEDA [Key Developer Data Encryption and Encryption Algorithm], The KDDEDA using to transmit confidential data for source to destination with speed data transmission and performance. KDDEDA also analyse encryption/decryption time, memory space, key size, block size and performance.